A modulated structure derived from the XA‐type Mn2RuSn Heusler compound. Issue 3 (26th May 2022) - Li, Xing-Zhong; Zhang, Wen-Yong; Skomski, Ralph; Sellmyer, David
Abstract : A new modulated structure derived from the XA‐type Mn2 RuSn Heusler compound has been observed and characterized. The structural model has been proposed on the basis of the unit cell of the XA phase and the antiphase boundary shift. Abstract : A modulated structure derived from the inverse Heusler phase (the XA‐type and the disordered variant L21 B‐type) has been observed in rapidly quenched Mn2 RuSn ribbons. The powder X‐ray diffraction pattern of the quenched ribbons can be indexed as an L21 B‐type structure. Electron diffraction patterns of the new structure mostly resemble those of the XA‐type (and the disordered variant L21 B‐type) structure and additional reflections with denser spacing indicate a long periodicity. Orthogonal domains of the modulated structure were revealed by a selected‐area electron diffraction pattern and the corresponding dark‐field transmission electron microscopy images. The structure was further studied by the crystallographic analysis of high‐resolution transmission electron microscopy images. A model for the modulated structure has been proposed to interpret the experimental results.